Echo and the Recovery of the Past in R. Murray Schafer’s The Princess of The Stars - Kinnear, Tyler (Intersections, 2018)
Canadian composer and acoustic ecologist R. Murray Schafer is known for his outdoor works. Other scholars have considered the collaboration between musicians and the physical world in Schafer’s compositions and have linked performer-environment interaction with Canadian identity and environmentalism. Yet the role and meaning of outdoor acoustics in Schafer’s music remains understudied. This article investigates the aesthetics of echo in Schafer’s outdoor theatre work The Princess of the Stars (1981–4). Echo not only sends an original sound back from a surface but also offers insight into the role that musical sounds play in prescribing an interpretation of nature.